Can tan theeta be integrated?, Mathematics

Ans)

You can integrate tanθ

write tanθ=sinθ/cosθ

so now, integral of tanθ.dθ=integral of sinθ/cosθ.dθ→1

put cosθ=t→2

there fore -sinθ.dθ=dt→3

put 2 and 3 in 1

so,the question becomes integral of tanθ.dθ=integral of -dt/t→4

=-log t +c      →   5                  [reason:dx/x=logx]

put 2 in 5,

 =-log cosθ+C

where C is the integration constant

Posted Date: 3/9/2013 7:30:02 AM | Location : United States





yes you can intergrate tan θ

 tan q = sin q/cos q (1)

let,

y = cos q

so, dy/dq = -sin q

this implies, dq=dy/-sin q  (2)

 

putting values in (1)

∫ 1/-y 

= -log|y|

=-log|cos q|

 so the ∫ tan q = -log|cos q|

Posted by | Posted Date: 3/9/2013 7:36:41 AM


Related Discussions:- Can tan theeta be integrated?, Assignment Help, Ask Question on Can tan theeta be integrated?, Get Answer, Expert's Help, Can tan theeta be integrated? Discussions

Write discussion on Can tan theeta be integrated?
Your posts are moderated
Related Questions
Use an appropriate infinite series method about x = 0 to find two solutions of the given differential equation: y''''-xy''-y=0

I had just come back from a very interesting talk arranged by a Mathematics Centre, it was aimed at parents of primary school-going children. They had talked about, and demonstrate

Application of Linear Equations We are going to talk about applications to linear equations.  Or, put in other terms, now we will start looking at story problems or word probl

Let Consider R A Χ B, S B Χ C be two relations. Then compositions of the relations S and R given by SoR A Χ C and is explained by (a, c) €(S o R) iff € b € B like (a, b) € R,

what is 8x6 is

how can I compare fractions with unlike denominators?

Estimation of difference among population proportions Assume the two proportions be described by P1 and P2, respectively,Then the difference absolute between the two proportion

to difine trigonometric ratios of an angle,is it necessary that the initial ray of the angle must be positive x-axis?


1. For a function f : Z → Z, let R be the relation on Z given by xRy iff f(x) = f(y). (a) Prove that R is an equivalence relation on Z. (b) If for every x ? Z, the equivalenc